Spices, Colonialism, and the Growth of New Economic Centers on the East Coast of East Sulawesi, 1620s—1920s - La Ode Rabani; Sarkawi B. Husain; Johny Alfian Khusyairi (Universitas Airlangga, 2022)
This study focuses on the East Coast of Sulawesi, which includes parts of the mainland and the eastern coast of Sulawesi Island. The area comprises parts of Central Sulawesi Â and Southeast Sulawesi, as well as surrounding islands such as Buton, Muna, Menui, Salabangka, and Siompu. The islands are significant in supporting economic activities along the spice route strip of the eastern coast of Sulawesi Island. The study explores the spice trade effect on the region in various aspects such as political, economic, social, cultural, and others. The research uses a historical method that focuses on relevant documents by conducting criticisms, interpretations, and analyses. The study found that spices that grow endemically and distinctly (exotic) in the archipelago (Banda Islands) have a long-lasting impact and cover various aspects. Spices had driven other nations to reach, exploit, and trade them to gain wealth and glory. For this reason, conflicts and wars have colored the history of spices that led to the practice of colonialism and hegemony. Colonial hegemony did not always have negative implications but also had essential effects on the growth of the region around the network of spice production centers as new economic centers on the East Coast of Sulawesi. The encounter between the indigenous people and other nations through the spice trade network had a significant positive impact, which Sartono Kartodirjo called positive integration.